Does Tai Chi improve psychological well-being and quality of life in patients with cardiovascular disease and/or cardiovascular risk factors? A systematic review protocol. Issue 8 (18th August 2017) - Yang, Guoyan; Li, Wenyuan; Cao, Huijuan; Klupp, Nerida; Liu, Jianping; Bensoussan, Alan; Kiat, Hosen; Chang, Dennis
Abstract : Introduction: Cardiovascular disease (CVD) is a leading cause of morbidity and mortality worldwide. Psychological risk factors such as stress, anxiety and depression are known to play a significant and independent role in the development and progression of CVD and its risk factors. Tai Chi has been reported to be potentially effective for health and well-being. It is of value to assess the effectiveness and safety of Tai Chi on psychological well-being and quality of life in people with CVD and/or cardiovascular risk factors. Methods and analysis: We will include all relevant randomised controlled trials on Tai Chi for stress, anxiety, depression, psychological well-being and quality of life in people with CVD and cardiovascular risk factors. Literature searching will be conducted until 31 December 2016 from major English and Chinese databases. Two authors will conduct data selection and extraction independently. Quality assessment will be conducted using the risk of bias tool recommended by the Cochrane Collaboration. We will conduct data analysis using Cochrane's RevMan software. Forest plots and summary of findings tables will illustrate the results from a meta-analysis if sufficient studies are identified. Ethics and dissemination: Ethics approval is not required as this study will not involve patients. The results of this study will be submitted to a peer-reviewed journal for publication, to inform both clinical practice and further research on Tai Chi and CVDs. Discussion: This review will summarise the evidence on Tai Chi for psychological well-being and quality of life in people with CVD and their risk factors. We anticipate that the results of this review would be useful for healthcare professionals and researchers on Tai Chi and CVDs. Trial registration number: International Prospective Register for Systematic Reviews (PROSPERO) number CRD42016042905.